Analisis Pengaruh Pertumbuhan Ekonomi, Upah Minimum Provinsi (UMP) dan Tingkat Pengangguran terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Fajriansyah, Saman; Chandriyati, Ika (PPJP ULM, 2022)
This study aims to determine the effect of economic growth, the provincial minimum wage (UMP), the open unemployment rate on the poverty level and which factors have the most dominant influence on the poverty level. The scope of this research took the area of South Kalimantan Province. The type of data used is secondary data obtained from literature sources and official data obtained from agencies related to this research which will be processed by multiple regression analysis and simultaneous and partial tests. The results of this study are economic growth, provincial minimum wages (UMP), the open unemployment rate simultaneously have a positive and significant effect on the poverty level and partially only economic growth has no effect on the poverty rate for other variables that affect the poverty level. The provincial minimum wage (UMP) is the most dominant factor affecting poverty levels.